Flegmasias de los miembros inferiores de origen no trombótico - Nozar, José; Delgado, Bolívar; Farcic, Antonio; Iraola, María L; Zimmer, Walter; Luvizio, José (Cirugía del Uruguay, 1978)
Case material consists of 5 cases of rapid onset of edema of a lower limb, with ali the characteristics of phlegmasia due to acute venous thrombosis, but which responded to a different pathogenesis. In one of these patients it had béen caused by artero-venous fistula between an aneurism of right primitive iliac artery and satellite vein. In the remaining 4, it had been due to compression of iliac vein of diverse origin. Diagnosis can be made by means of phlebography. According to the authors there is a difference between the phlebographic image due to compression and that due to thrombosis. In the former the absence of filling in the venoüs path presents marked edges and arways has a narrow passage with filling of venous trunk above the compression. In cases cf acute thrombosis there is total venous obliteration, no passage to proximal vein and there is collateral derivation. In view of the possibi!ity of diagnostica! error, the authors believe that no venous thrombectomy should be peformed without prior phlebography.